Cracked credibility. (Economist, 2013)
The article looks at internet encryption as of September 2013. Topics include the efforts of the U.S. National Security Agency (NSA) and the British Government Communications Headquarters (GCHQ) to sabotage internet encryption codes, the use of "backdoors" that allow interested parties to infiltrate a user's encrypted online interactions, and the danger posed to technology firms such as Google.